Wikipedia and Historiography: The Case of Singapore and the Philippines Compared - Luyt, Brendan (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper explores the intellectual space of Wikipedia history-writing and raises questions about the nature of the relationship between this new virtual territory and the world of older print media history-writing using as examples the pages devoted to the national histories of the Philippines and Singapore. Cet article explore l’espace intellectuel que constitue Wikipédia dans la rédaction de l’histoire et questionne la nature du lien entre ce nouveau territoire virtuel et le monde traditionnel de l’imprimé. Seront examinées en exemple les pages consacrées à l’histoire nationale des Philippines et de Singapour.